Design Information System Stock Inventory To Manage Data Of Goods (Case Study: PT Monier) - Supriyanti, Dedeh; Kesumawati, Christien Setiya; Maryam, Siti (Pandawan, 2020)
Application of information system on the inventory will provide many benefits for the company in developing company in order to improve the company's performance become more effective and efficient. This research was conducted at manufacturing companies, to know overall about inventory items in the company. The purpose of this research is to find out the effectiveness of the inventory as a resource physical economy that needs to be held and maintained in order to support the process booking goods and sales in progress PT Monier. PT Monier is as a company manufacturers concrete roofing materials with the production system where the process for creating objects with cross-section of fixed. The methods of analysis used is descriptive data analysis method. Engineering data collection with do the observations to the company, conducting interviews, and route the study library with books, the literary, the materials gained during lectures relevant to the problems examined. Research results shows that the control of inventory items It often happens booking of the goods to the supplier in excess inventory and the shortage of supplies. Due to the lack of regard for the State of inventory items. Inventory data input errors often occur more than once for similar goods give rise to errors in reporting. Then the author here attempted to analyze the problems against information systems inventory items and to find solutions to the fore of the existing problems by fixing a system that is less than optimal.